Arti Persahabatan dalam Film kartun Motu Patlu Prespektif Pendidikan Islam - Salis Irvan Fuadi; Robingun Suyud El Syam; Roni Muslikah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The cartoon film Motu Patlu is watched by all groups. The unique and funny characters, as well as the exciting stories, make this cartoon series even more popular with viewers. However, the less educational aspects in it meant that the film was banned from being shown on television in various countries, including Indonesia. The purpose of this article is to highlight the meaning of Motu Patlu friendship in Islamic education, which has never been seen before. The results of the study show that Motu Patlu's friendship occurs to complement each other, where Motu is a character who cannot think when he is hungry. As for Patlu, a character who, when faced with problems, will actually come up with an idea. The combination of the two has an effect on the success of a mission. It's worth noting. that the mission in the film cannot be separated from the theme of helping or eradicating crime. This study provides a valuable contribution to understanding why friendship is important. This study also highlights the importance of friendship, for a positive purpose, thereby advancing current knowledge about this object.